Implementasi Digital Marketing Produk Batik Ngangkrik-Madiun sebagai Solusi Komunikasi Pemasaran Modern - Slamet Riyanto; Muh Nur Luthfi Aziz; Latjuba Sofyan STT; Yoga Prisma Yuda (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2024)
The purpose of this activity is to find out the implementation of digital marketing for Batik Ngangkrik products as a form of modern marketing communication solutions. The forms of this activity include product photos, online store creation, dissemination of the use of digital marketing and promotions in the form of digital content. The results of this activity indicate that digital marketing activities for Ngangkrik batik products have not yielded significant results in supporting the marketing and sales of batik products. This is because the intensity of promotion through digital content on social media has not run optimally. In addition, the community service team still has difficulty identifying or highlighting the product value of Ngangkrik batik. Furthermore, it is necessary to carry out promotional activities by creating various digital content by utilizing paid Ads on social media